Propagation of changes in demand through international trade: Case study China - Jochen Andritzky; Bernhard Kassner; Wolf Heinrich Reuter (Sachverständigenrat zur Begutachtung der Gesamtwirtschaftlichen Entwicklung, 2016)
China's economy, the second largest in the world, is undergoing a fundamental transition. Its transition from a strong focus on investment and exports towards a larger share of consumption could have important ramifications for China's trading partners. Using China as a case study, this paper deploys a sectoral input-output (IO) analysis to take into account higher-round spillovers from a reduction in import demand or a shift in the composition of the Chinese economy. This approach demonstrates strong indirect effects that exceed by far the initial shock from direct trade links, reflecting China's integration into a closely knit global value chain. The result suggests that the ongoing transition in China will have important effects on the global economy.
Keywords: F14; C67; F47; 330; Shock propagation; Trade channel; Input-Output; China